DIGITAL SOUNDSCAPES OF WELL-BEING: A STUDY OF POSITIVE PSYCHOLOGICAL OUTCOMES OF MOTIVATIONAL PODCAST CONSUMPTION - M., Venkates; Sripriya M.; N., Rajkamal (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Purpose: This research examined the effect of motivational podcasts in Tamil on the positive psychological well-being of Tamil college students in Tamil Nadu. It analyses the way in which exposure to motivational audio material, especially Oru Cup Confidence, Maname Nalama, and Leader - Rajmohan can result in optimism, resilience, and self-efficacy through Positive Psychology Seligman and Csikszentmihalyi (2000). Design/Methodology/Approach: Quantitative cross-sectional design was adopted and 250 college students of Coimbatore, Tamil Nadu were involved. A structured questionnaire on frequency of podcast listening, optimism, resilience and self-efficacy was used to gather data between June and October 2025 on a five-point Likert scale. The correlational and regression analysis was used to study the relationships between the listening to the podcast and well-being outcomes. Findings: The findings showed a high positive relationship between motivational podcast listening and psychological well-being (r =.62, p <.001). It was found that optimism, resilience and self-efficacy were greatly predicted by listening frequency (b =.58, p <.001). Emotional stability and goal orientation were higher among regular listeners than occasional and random listeners. Originality/Value: This study offers factual information regarding the psychological strength and hope in the minds of young people through Tamil inspirational podcasts. This highlights the promise of vernacular digital media as a tool of mental wellness promotion of students in India that can be affordable and culturally relevant at the same time.